СЕМАНТИКА НОМИНАЦИЙ С ОСНОВНЫМ КОМПОНЕНТОМ ӨЛ «УМЕРЕТЬ» (НА МАТЕРИАЛЕ ЯКУТСКОГО ЯЗЫКА) - Pavlova, Irina Petrovna; Rozhina, Evgenia Alekseevna (Sovremennye issledovaniya sotsialnykh problem, 2016)
Цель. Статья посвящена исследованию группы слов с общей семантикой “умереть” (өлбүт) и “умерший”(өлбүт) в якутском языке. Авторы ставят целью раскрыть общие закономерности образования языковых единиц в критических ситуациях, в том числе таких, как болезнь, смерть и других.Метод. Основу исследования образует метод сплошной выборки.Результаты. Авторы приходят к выводу, что семантика номинаций с основным компонентом өлбүт «умер” демонстрирует общие закономерности образования слов. Каждый народ воспринимает окружающий его мир сквозь призму своих культурных обычаев, нравственных установок и принятых традиций.Область применения результатов. Результаты исследования могут быть использованы при составлении толковых, этимологических, этнолингвистических и иных словарей, а также при разработке практических пособий, спецкурсов по фольклору, лексикологии, этнографии и культурологии. Purpose. The article is devoted to the research of a group of words with a common meaning “die” (өlbүt) and “deceased” (өlbүt) in the Yakut language. The authors set the goal to disclose the general regularities on formation of linguistic units in critical emergency, including situations such as illness, death, etc.Method. The continuous sampling and descriptive methods are used during the research.Results. The authors conclude that the semantics of the nominations with the main component өlbүt “died” shows the general laws of words formation. The semantics of the nominations with the main component өl “to die” has national-specific features: each nation perceives the world around through the prism of their own cultural customs, moral principles, and accepted traditions.Results application. Results of the research can be used to compile explanatory, etymological, ethnic-and-linguistic and other dictionaries, as well as develop workbooks and specialty courses on folklore, lexicography, ethnography and cultural studies.